IJCM_60A: Menstrual hygiene management practices in tribal areas of Mysore district: A cross-sectional study - Anila P; Khan Mudassir Azeez (Wolters Kluwer Medknow Publications, 2024)
Background: Menstrual Health Management is defined as women and adolescent girls using a clean menstrual management material to absorb or collect blood that can be changed in privacy as often as necessary for the duration of menstruation period, using soap and water for washing the body as required and having access to facilities to dispose of menstrual management materials. Since considerable amount of tribal population belong to Mysore district it is important to study the practices among the most vulnerable population. Objectives: 1. To estimate the knowledge on menstrual hygiene among the study population. 2. To measure the impact of socio-demographic and cultural determinants on menstrual hygiene management practices among the study population. Methodology: A community based cross-sectional study on menstruating women residing in tribal areas of Mysuru district was conducted from July to September 2023. Sample size was calculated using single proportion formula and it was estimated to be 130. All menstruating women/girls who were present during the time of visit were included in the study after getting their consent/ ascent. Multistage sampling was adopted to select the study participants. A validated semi-structured questionnaire was used for collection of data. Data was entered in MS Excel and analysed using SPSS v29 trial version. Results: 99% of the study population knew that menstruation is a physiological process and poor menstrual hygiene causes urinary and reproductive tract infections. More than 80% of the study population have access to sanitary napkins for managing their menstrual cycles. Conclusion: Majority of the study participants are aware about menstruation as a physiological process and have access to sanitary napkins for management. But the disposal of sanitary waste and cultural barriers that persists in the society are still existing as a roadblock for improving reproductive health.